(untitled) (International Journal on Stereo & Immersive Media, 2025)
Bridging interdisciplinary perspectives, this article presents the kaleidoscope as a significant case study of self-directed perceptual technology in the history of immersive media. Using a media-archaeological approach, the study traces the device’s journey from Sir David Brewster’s 19th-century optical invention to its roles in contemporary therapy and immersive art. The article argues that the kaleidoscope endures because it mediates a recursive relationship between agency and perception—specifically through the interplay of tactile control, visual symmetry, and temporal fluidity. By contrasting the device with representational peep media, the analysis shows how it generates endless, abstract, non-narrative images that foster an embodied experience and cognitive regulation. This mechanism is explored across diverse contexts from its controversial beginnings as a ‘philosophical instrument’ to its clinical validation as a tool for reducing anxiety, to its transformation in large-scale installations by artists like Olafur Eliasson and teamLab. In these modern works, the principle of self-directed seeing evolves from tactile manipulation to viewer mobility. Ultimately, this study posits the kaleidoscope as a foundational ancestor of contemporary immersive technologies.